2009
DOI: 10.1021/pr9000898
|View full text |Cite
|
Sign up to set email alerts
|

Global Histone Analysis by Mass Spectrometry Reveals a High Content of Acetylated Lysine Residues in the Malaria Parasite Plasmodium falciparum

Abstract: Post-translational modifications (PTMs) of histone tails play a key role in epigenetic regulation of gene expression in a range of organisms from yeast to human; however, little is known about histone proteins from the parasite that causes malaria in humans, Plasmodium falciparum. We characterized P. falciparum histone PTMs using advanced mass spectrometry driven proteomics. Acid-extracted proteins were resolved in SDS-PAGE, in-gel trypsin digested, and analyzed by reversed-phase LC-MS/MS. Through the combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
196
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(208 citation statements)
references
References 69 publications
11
196
0
1
Order By: Relevance
“…For example, expression of variant surface antigen gene families (7) and ligands involved in parasite red blood cell (RBC) invasion (8) are controlled by histone acetylation and methylation marks. Apicomplexan parasites, including Plasmodium and Toxoplasma, possess orthologs to many chromatin remodeling proteins and enzymes responsible for histone modifications (9-11), and many conserved posttranslational modifications have been identified on P. falciparum histones (12). Genome-wide high-resolution ChIP-on-chip analysis revealed that the generally activating histone modifications trimethyl histone H3 lysine 4 (H3K4me3) and acetyl histone H3 lysine 9 (H3K9ac) are located throughout the parasite genome (13,14).…”
mentioning
confidence: 99%
“…For example, expression of variant surface antigen gene families (7) and ligands involved in parasite red blood cell (RBC) invasion (8) are controlled by histone acetylation and methylation marks. Apicomplexan parasites, including Plasmodium and Toxoplasma, possess orthologs to many chromatin remodeling proteins and enzymes responsible for histone modifications (9-11), and many conserved posttranslational modifications have been identified on P. falciparum histones (12). Genome-wide high-resolution ChIP-on-chip analysis revealed that the generally activating histone modifications trimethyl histone H3 lysine 4 (H3K4me3) and acetyl histone H3 lysine 9 (H3K9ac) are located throughout the parasite genome (13,14).…”
mentioning
confidence: 99%
“…about 2% of the total protein-coding genes of P. falciparum). By contrast, only a few substrates for ubiquitylation have been identified in P. falciparum, including actin (12) and the histone protein H2B (13). The quickly reversible character of ubiquitylation (intervention of deubiquitinases) and the rapid degradation of polyubiquitylated proteins (proteasome) render the isolation and analysis of ubiquitylated proteins challenging.…”
mentioning
confidence: 99%
“…The detection and identification of methylated peptides can be validated by the observation of these characteristic marker ions or neutral loss, particularly in the cases that the MS/MS fragmentation patterns are insufficient to determine the nature of the modification. 137,138 In addition to the validation of sequencing data, the marker ions can also be utilized in the discovery of methylated peptides. In "immonium ion scanning" method, modified peptides can be specifically selected by monitoring their characteristic immonium ion(s) using tandem mass spectrometers, such as triple quadrupole instruments.…”
Section: A Ms Methods For the Detection And Site Mapping Of Histone mentioning
confidence: 99%
“…137,138 Fragmentation of trimethylated peptides usually generates a neutral loss of trimethyl amine at 59 Da whereas an acetylated peptide produces an ammonium ion at 126 Da during collision induced dissociation. 135 A recent example reported by Trelle and coworkers reveals the distinction of H3K9 acetylation and H3K9 trimethylation in P. falciparum.…”
Section: A Ms Methods For the Detection And Site Mapping Of Histone mentioning
confidence: 99%
See 1 more Smart Citation